Use of compensation theorem for the robustness assessment of electromagnetic devices optimal design. Issue 3 (29th April 2014) - Formisano, Alessandro; Fresa, Raffaele; Martone, Raffaele
Abstract : Purpose: – The purpose of this paper is to present the use of the compensation theorem (CT), well known in the analysis of linear electric networks, to compute sensitivity of the performance functions used in the robust design or tolerance analysis of electromagnetic devices. Design/methodology/approach: – The CT is first illustrated in the case of a simple field analysis problem. Then, using numerical simulations, the effectiveness of compensation approach for assessing impact of the small modification of material properties is shown. The numerical simulations are performed with a finite elements code based on an integral formulation. Findings: – The complexity of additional computations to assess the effect of small variations involved in sensitivity analysis can be reduced. Research limitations/implications: – The method can be applied only to linear systems; in addition, although compensation applies to any variations, the reduction of computational complexity is achieved only for small variations, giving localized effects. Practical implications: – The method proposed in the paper can speed up the computations of sensitivity arrays in the robust design and tolerance analysis of electromagnetic device, when numerical methods are applied. Originality/value: – The use of CT in field computations is not new, but its adoption in the sensitivity computation is new to the best knowledge of authors.